Gambaran Kecemasan Efek Hospitalisasi pada Anak Prasekolah di Ruang Parkit Rumah Sakit Qolbu Insan Mulia Batang - Okie Pujianti, Okie Pujianti; Herry Susanto; Kurnia Wijayanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Hospitalization in preschool children often causes anxiety due to several factors, such as unfamiliar environments, uncomfortable medical procedures, and separation from parents. This condition can negatively affect the child’s psychological state, which may influence both the healing process and adaptation during hospital care. Therefore, it is important to understand the description of anxiety experienced by children during hospitalization so that health workers can provide appropriate interventions. This study aimed to describe the anxiety caused by hospitalization among preschool children admitted to the Parkit Ward of Qolbu Insan Mulia (QIM) Hospital Batang. The study employed a descriptive quantitative design with a purposive sampling technique. A total of 65 preschool children aged 3–6 years who met the inclusion criteria were recruited as samples. The instrument used was the Spence Children’s Anxiety Scale (SCAS) Preschool Parent Report, which was completed by parents to assess the children’s level of anxiety. Data analysis was carried out using frequency distribution to present both the respondents’ characteristics and the level of anxiety. The results showed that most respondents were 5 years old (36.9%) and predominantly male (61.5%). A majority of the respondents had never been hospitalized before (63.1%), making hospitalization a first-time experience that could trigger anxiety. The highest proportion of anxiety levels was in the mild category (38.4%), followed by moderate anxiety (30.7%). Only a small proportion of children experienced severe anxiety. In conclusion, preschool children undergoing hospitalization in the Parkit Ward of QIM Hospital Batang mostly experienced mild to moderate anxiety. These findings provide an important overview for nursing staff in designing interventions to reduce children’s anxiety. Suggested approaches include play therapy, effective communication, and active parental involvement in the care process. With such strategies, it is expected that children’s anxiety can be reduced, making hospitalization a more adaptive experience that supports the recovery process.